2002
DOI: 10.1007/s10350-004-6231-z
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of Peritonitis by Peritoneal Cytokine Measurement

Abstract: We suggest that the estimation of the peritoneal cytokine levels might be an additional diagnostic tool that can support the early recognition of peritonitic complications in colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 14 publications
(22 reference statements)
4
61
0
8
Order By: Relevance
“…We believe that the first peak at 6 hours was associated with the initiation of the inflammatory response that is naturally accompanied by the increased expression of proinflammatory ILs. (2,3) This observation coincides with the opinion of other authors concerning the key role that injury plays in the production of proinflammatory cytokines during the early period after peritoneal damage. (6,10) The second peak most likely reflects the work of the key elements of the reparative process; specifically, day 3 is the start of the fibroblastic phase of inflammation during aseptic wound healing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We believe that the first peak at 6 hours was associated with the initiation of the inflammatory response that is naturally accompanied by the increased expression of proinflammatory ILs. (2,3) This observation coincides with the opinion of other authors concerning the key role that injury plays in the production of proinflammatory cytokines during the early period after peritoneal damage. (6,10) The second peak most likely reflects the work of the key elements of the reparative process; specifically, day 3 is the start of the fibroblastic phase of inflammation during aseptic wound healing.…”
Section: Discussionsupporting
confidence: 90%
“…TNFα and IL1β are the early regulators of the immune response and induce the release of secondary cytokines such as IL6 and IL8. (2,3) Currently, the data on the correlation between the concentration of cytokines in plasma and peritoneal fluid are contradictory. Most researchers have observed an increase in cytokine concentration in the zone of damage compared with the concentration of serum cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…inhibitorów proteinazy, dopełniacza, białek układu krzepnięcia, białka ostrej fazy (C-reactive protein -CRP), a ponadto gorączką oraz leukocytozą [21,22]. Miejscowy odczyn w odpowiedzi na wniknięcie bakterii do jamy otrzewnowej to głównie funkcja fagocytarna leukocytów oraz makrofagów.…”
Section: Patofizjologiaunclassified
“…Another important healing parameter is cytokine expression in the anastomotic area. Several authors have assessed cytokine levels in the postoperative period and their relationship to anastomotic complications [4][5][6][7] . During the healing process, cytokines and chemokines interact to determine the strength of the inflammatory response and the extent of subsequent adhesion formation 8 .…”
Section: Introductionmentioning
confidence: 99%
“…After trauma, cytokines are primarily synthesized and released at the site of injury and subsequently released Herwig et al 4 showed that a marked increase in IL-6 and TNF-α levels may be considered a precursor event occurring days before the secondary clinical signs of anastomotic leakage and that the increase in IL-1β cytokine levels became statistically significant on the 3rd POD in patients who had anastomotic dehiscence. Also, a positive correlation has been described between IL-1β, IL-6…”
mentioning
confidence: 99%